Agency Theory and Its Application to Small Firms: Evidence from the Swedish Venture Capital Market - Hans Landstrom (Journal of Small Business Finance, 1993)
The research in small firms financing is characterized by a lack of a theoretical framework. One basic assumption in this study is that agency theory can provide an essential framework to explain the interaction between informal and formal venture capitalists and their portfolio firms. Five hypotheses generated from agency theory are formulated and tested on 62 firms backed by informal venture capitalists and 145 firms backed by formal venture capitalists. The theoretical conclusion is that agency theory does not provide a satisfactory framework to explain either the informal venture capitalist's, nor the formal venture capitalist's relationship to their portfolio firms. Therefore, more exploratory research must be done to develop a theory of finance which will be applicable in the small firms situation.
Keywords: G24; L25; G32; 650; Capital; Venture Capital; Agency Theory; Small Firms; Small Business; Sweden